Diagnostic Challenge in a Case of Cryptogenic Organising Pneumonia - Shailesh Bhanudas Meshram; Brahmansh Singh; Rishi Govind Orakkan; Shrividya Sethuratnam (Journal of Clinical and Diagnostic Research)
Cryptogenic Organising Pneumonia (COP) is a rare Interstitial Lung Disease (ILD) characterised by a distinctive histological pattern without a known cause. It was earlier referred to as bronchiolitis obliterans organising pneumonia and is brought on by alveolar damage, which causes organised granulation tissue to form, resulting in the blockage of alveoli and bronchioles. If left untreated, the obstructions may cause progressive respiratory failure. This case report describes a 65-year-old female who exhibited respiratory symptoms like low-grade fever, dry cough, poor appetite and loss of weight for about one month, alongside radiological characteristics resembling lung malignancy. The imaging studies showed a dense, irregular opacity with spiculations in the left lung field, leading to a potential misdiagnosis. Comprehensive evaluation, including fibreoptic bronchoscopy which aided in obtaining a Transbronchial Lung Biopsy (TBLB) sample for histopathological examination, revealed alveolar spaces containing foamy macrophages, neutrophils and intra-alveolar plugs of fibroblastic tissue all typical of COP, leading to its diagnosis. Despite the initial challenges posed by the puzzling radiological features, a prompt and accurate diagnosis rooted in histopathology allowed for timely corticosteroid treatment. This case highlights the diagnostic challenges posed by the overlap of radiological attributes between COP and lung malignancy, emphasising the need for careful assessment to avoid multiple unnecessary invasive procedures and delays in treatment. It also underlines the utility of a nuanced histopathological study. Awareness of COP’s clinical and radiological similarities to malignancy and a comprehensive diagnostic approach in such cases is essential for reliable diagnosis, effective patient management and good prognosis.